Determinants of a Consumer's Intention to Consume Antioxidant-infused Sugar-free Chewing Gum: Measuring Taste, Attitude, and Health Consciousness. Issue 1 (2nd January 2020) - Jung, Seung Eun; Shin, Yeon Ho; Severt, Kimberly; Crowe-White, Kristi M
ABSTRACT: The purpose of this study was to identify predictors of consumers' intention to purchase antioxidant-infused sugar-free chewing gum for vascular health by utilizing the Value Attitude Behavior model. In this cross-sectional study, a total of 368 young adults completed a validated survey instrument measuring attitude, health consciousness, intention, and perceived taste of the functional gum. Structural equation modeling was used to analyze data. Regarding the total effect of health consciousness, perceived taste, and attitude on intention, perceived taste was the most powerful predictors followed by attitude and health consciousness in determining consumers' intention to purchase antioxidant-infused sugar-free chewing gum. From an implication standpoint, marketing the health benefits of chewing antioxidant-infused sugar-free chewing gum along with providing good taste, and highlighting the importance of developing positive attitudes, is critical to the success of this functional product in the marketplace.